2011
DOI: 10.5194/acp-11-7417-2011
|View full text |Cite
|
Sign up to set email alerts
|

The Pasadena Aerosol Characterization Observatory (PACO): chemical and physical analysis of the Western Los Angeles basin aerosol

Abstract: Abstract. The Pasadena Aerosol Characterization Observatory (PACO) represents the first major aerosol characterization experiment centered in the Western/Central Los Angeles Basin. The sampling site, located on the campus of the California Institute of Technology in Pasadena, was positioned to sample a continuous afternoon influx of transported urban aerosol with a photochemical age of 1-2 h and generally free from major local contributions. Sampling spanned 5 months during the summer of 2009, which were broke… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
108
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 75 publications
16
108
3
Order By: Relevance
“…LV, SV-OOA) correlate well with secondary sulphate (Huang et al, 2011;Hersey et al, 2011), from which a secondary source is inferred. However in this study the organic uptake is demonstrated to be both proportional to the SO 4 mass and with relatively high O : C ratios, which implies that a fraction of the measured oxygenated OA, which correlates with secondary sulphate and assigned as SOA, may in fact be primary in nature.…”
Section: Implications and Conclusionmentioning
confidence: 62%
“…LV, SV-OOA) correlate well with secondary sulphate (Huang et al, 2011;Hersey et al, 2011), from which a secondary source is inferred. However in this study the organic uptake is demonstrated to be both proportional to the SO 4 mass and with relatively high O : C ratios, which implies that a fraction of the measured oxygenated OA, which correlates with secondary sulphate and assigned as SOA, may in fact be primary in nature.…”
Section: Implications and Conclusionmentioning
confidence: 62%
“…[82] In recent years, positive matrix factorisation (PMF) analysis has become a common tool for AMS data analysis and provided valuable information about sources of OAs and their atmospheric evolution at many locations affected by anthropogenic emissions. [83] Specifically, a hydrocarbon-like OA (HOA) factor was attributed to primary aerosols emissions associated with urban traffic, [84][85][86][87][88][89][90] residential heating using solid fuel and wood, [86][87][88] fossil fuel combustion and biomass burning [84] and food cooking and charbroiling. [87] The HOA factor was minor in AMS datasets collected in remote and rural areas.…”
Section: Field and Test Facilities Studies Anthropogenic Aerosolsmentioning
confidence: 99%
“…Semi-volatile and low-volatility OOA (SV-OOA and LV-SOA) factors were commonly reported and apportioned to fresh and atmospherically aged anthropogenic SOAs respectively. [82][83][84][85][86][87][88][89][90][91][92] Narrowly focussed, source-specific factors, such as cooking OAs, [87] biomass burning OAs (BBOAs), [84,88] solid fuel OAs [86] and amine-containing OAs, [91] were also reported in some studies. Furthermore, Sun et al [93] recently conducted analysis of water-soluble organic carbon (WSOC), where the AMS measurements and the PMF data analysis were applied to interrogate aerosolised mist of aqueous extracts from filter samples.…”
Section: Field and Test Facilities Studies Anthropogenic Aerosolsmentioning
confidence: 99%
“…The full HR-ToF-AMS spectrum, over the course of SOA formation and evolution, comprises a large number of massto-charge ratios (m/z), which contain time-dependent information on the overall processes occurring. Positive Matrix Factorization (PMF) has proved to be a powerful procedure for analyzing HR-ToF-AMS spectra in terms of the evolution of major mass spectral factors (Lanz et al, 2007;Aiken et al, 2009;Ng et al, 2010;Hersey et al, 2011;Fry et al, 2011). The factor profile extracts the contributions from a number of masses that are co-correlated, providing information on the time evolution of the aerosol composition that is not immediately evident from the complex aerosol spectrum.…”
Section: J S Craven Et Al: Analysis Of Secondary Organic Aerosol Fmentioning
confidence: 99%
“…Positive Matrix Factorization (PMF) has emerged as a powerful technique for source apportionment of HR-ToF-AMS measurements of ambient aerosol (Paatero and Tapper, 1994;Jimenez et al, 2009;Lanz et al, 2007;Aiken et al, 2009;Hersey et al, 2011;Ng et al, 2010;Allan, 2003;Zhang et al, 2011). Here, the application of PMF to HR-ToF-AMS spectra to investigate SOA formation in a laboratory chamber is reported for the first time.…”
Section: Positive Matrix Factorization (Pmf)mentioning
confidence: 99%